The relationship between corporate governance mechanisms and going concern evaluation: Evidence from firms listed on Amman Stock Exchange - Zureigat, Bilal Nayef; Fadzil, Faudziah Hanim; Syed Ismail, Syed Soffian (Macrothink Institute, 2014)
This study aims to examine the relationship between corporate governance mechanisms (representative by each of managerial, institutional ownership, board independence and board meeting) and going concern evaluation among Jordanian listed firms. Through using multiple regression analysis, the results of this study illustrates that there is a positive relationship between managerial ownership, board independence and board meeting and going-concern evaluation, while a negative relationship is found with institutional ownership.There are four main hypotheses, two of them which are managerial and institutional ownership are accepted, while board independence and board meeting are not supported. This study shed more light on the importance of complying with the requirements of governance code and instructions by the companies and the need to impose fines or sanctions on non-compliant companies.The results of this study contribute to the creditors‟ interest to be more alert to companies which may possess characteristics that contribute in manipulation of future companies.